2015
DOI: 10.1371/journal.pone.0118142
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ahmed Glaucoma Valve Implantation and Trabeculectomy for Glaucoma: A Systematic Review and Meta-Analysis

Abstract: ObjectiveTo compare the efficacy and safety of Ahmed glaucoma valve implantation (AGV) with trabeculectomy in the management of glaucoma patients.MethodsA comprehensive literature search (PubMed, Embase, Google, and the Cochrane library) was performed, including a systematic review with meta-analysis of controlled clinical trials comparing AGV versus trabeculectomy. Efficacy estimates were the weighted mean differences (WMDs) for the percentage intraocular pressure reduction (IOPR %) from baseline to end-point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“…During the 12-month follow-up, there were no cases of suprachoroidal hemorrhage, diplopia, severe corneal issues, retinal detachment, flat anterior chamber, choroidal effusion requiring drainage, loss of light perception, blebitis, iritis, endophthalmitis, hypotony maculopathy, or device obstruction, all of which have been reported with other glaucoma aqueous shunts. 29,[39][40][41][42][43][44][45][46][47][48][49] The AEs most commonly reported in this study were needling, BCVA loss of > _2 lines (of which 81% self-resolved), transient hypotony (requiring no surgical intervention but captured as AEs per protocol regardless of outcome), increased IOP, and glaucoma-related secondary surgical intervention. None, however, were unexpected in this population of patients with refractory glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…During the 12-month follow-up, there were no cases of suprachoroidal hemorrhage, diplopia, severe corneal issues, retinal detachment, flat anterior chamber, choroidal effusion requiring drainage, loss of light perception, blebitis, iritis, endophthalmitis, hypotony maculopathy, or device obstruction, all of which have been reported with other glaucoma aqueous shunts. 29,[39][40][41][42][43][44][45][46][47][48][49] The AEs most commonly reported in this study were needling, BCVA loss of > _2 lines (of which 81% self-resolved), transient hypotony (requiring no surgical intervention but captured as AEs per protocol regardless of outcome), increased IOP, and glaucoma-related secondary surgical intervention. None, however, were unexpected in this population of patients with refractory glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Outside of Cochrane reviews, one systematic review compared the Ahmed implant to trabeculectomy with or without MMC for glaucoma (HaiBo 2015). This review included a combination of prospective and retrospective studies and analyzed six studies with a total of 507 eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike our present review, this review reported that the Ahmed implant was equivalent to trabeculectomy for reduction of IOP and reduction of glaucoma medication usage, and that the Ahmed implant was associated with a lower frequency of adverse events compared with trabeculectomy. The HaiBo 2015 review is limited by its inclusion of retrospective studies with variable duration of follow-up, and is also potentially biased by its inclusion of a study that only included participants with neovascular glaucoma, as these patients are known to have higher risks of complications and poorer outcomes overall compared with people with non-neovascular glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…23 Notwithstanding, this review compared studies investigating a heterogeneous group of patients, including primary surgeries, eyes with neovascular glaucoma, aphakic glaucoma, and postcyclophotocoagulation. In fact, the vast majority of studies evaluating the performance of drainage implants involve a mix of refractory cases, with few studies evaluating a homogeneous group of eyes with lower risk for surgical failure.…”
Section: Discussionmentioning
confidence: 99%